Identifying and assessing environmental awareness of hotel and restaurant employees’ attitudes in the Amasra District of Bartin - Yucedag, Cengiz; Kaya, Latif Gurkan; Cetin, Mehmet (Springer Science and Business Media LLC, 2018)
Environmental damage occurring on individual, institutional, and societal levels is one of the major problems in the world and results from mostly unconscious human behavior. This damage poses serious threats to human health and other habitats. The aim of this study is to determine the level of environmental awareness of hotel and restaurant employees in the Amasra District of Bartin, Turkey. For this purpose, a descriptive survey method is used to measure 16 items with a 5-point Likert scale. Data are obtained from 200 employees in the hotels and restaurants as of 2015. The reliability coefficient is found to be 0.74. This data reveals that only 43% of hotels and 72% of restaurants in Amasra have recycling bins. Males and Bachelor's degree holders have more environmental awareness. Enterprises established after 2011 follow popular journals related to environment more than those before 2011. As a result, it is essential to organize educational meetings and seminars related to environmental awareness for hotel and restaurant employees in order to improve the tourism industry's environmental impact. The results show that the legislation has resulted in general environmental awareness and that the organizations are willing to change their business processes and environmental strategies. Nevertheless, despite their actions, there is little awareness of the benefits that can result from cost reductions resulting from environmentally friendly practices. Those affected by their suppliers act to reduce waste but do not deploy formal environmental management systems or use environmental messages to market their goods or services.
Keywords: Male; Restaurants; Turkey; Commerce; Reproducibility of Results; Environment; Attitude; Surveys and Questionnaires; Humans; Industry; Female; Environmental Monitoring; 3. Good health; 12. Responsible consumption; 13. Climate action; 11. Sustainability